The Potassium SK Channel Activator NS309 Protects Against Experimental Traumatic Brain Injury Through Anti-Inflammatory and Immunomodulatory Mechanisms - Chen, Tao; Zhu, Jie; Hang, Chun-Hua; Wang, Yu-Hai (Frontiers in Pharmacology, 2019)
Traumatic brain injury (TBI) remains the major cause of death and disability worldwide. Neuroinflammation plays important roles in neuronal cell death and functional deficits after TBI. Small conductance Ca2+-activated K+ channels (SK) have been shown to be potential therapeutic targets for treatment of neurological disorders, such as stroke and Parkinson’s disease (PD). The aim of the present study was to investigate the role of SK channels in an animal model of TBI induced by controlled cortical impact (CCI). The SK channels activator NS309 at a concentration of 2 mg/kg was administered by intraperitoneal injection, and no obviously organ-related toxicity of NS309 was found in Sprague-Dawley (SD) rats. Treatment with NS309 significantly reduced brain edema after TBI, but had no effect on contusion volume. This protection can be observed even when the administration was delayed by 4 h after injury. NS309 attenuated the TBI-induced deficits in motor and memory function, which was accompanied by the reduced neuronal apoptosis. The results of immunohistochemistry showed that NS309 decreased the number of neutrophils, lymphocytes and microglia cells, with no effect on astrocytes. In addition, NS309 markedly decreased the levels of pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) and chemokines (MCP-1, MIP-2 and RANTES), but increased the levels of anti-inflammatory cytokines (IL-4, IL-10 and TGF-β1) after TBI. The results of RT-PCR and western blot showed that NS309 increased TSG-6 expression and inhibited NF-κB activation. Furthermore, knockdown of TSG-6 using in vivo transfection with TSG-6 specific shRNA partially reversed the protective and anti-inflammatory effects of NS309 against TBI. In summary, our results indicate that the SK channel activator NS309 could modulate inflammation-associated immune cells and cytokines via regulating the STG-6/NF-κB pathway after TBI. The present study offers a new sight into the mechanisms responsible for SK channels activation with implications for the treatment of TBI.